2017
DOI: 10.3389/fmicb.2017.01928
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Resistance of UV- or Chlorine Dioxide-Resistant Echovirus 11 to Other Disinfectants

Abstract: The emergence of waterborne viruses with resistance to disinfection has been demonstrated in the laboratory and in the environment. Yet, the implications of such resistance for virus control remain obscure. In this study we investigate if viruses with resistance to a given disinfection method exhibit cross-resistance to other disinfectants. Chlorine dioxide (ClO2)- or UV-resistant populations of echovirus 11 were exposed to five inactivating treatments (free chlorine, ClO2, UV radiation, sunlight, and heat), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 48 publications
0
50
0
Order By: Relevance
“…In comparison, qPCR in the literature reports a reduction of genome integrity by UV 254 that is approximately equivalent to the loss of virus infectivity (5,18,27), implying a minimal contribution of protein damage to overall virus inactivation. While this is ideal for studies wishing to use qPCR tools as a rapid alternative to cell culture for estimating loss of infectivity, from a mechanistic standpoint these data diminish the importance of potential protein damage, which, based on the present study, may play a larger role than previously concluded.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In comparison, qPCR in the literature reports a reduction of genome integrity by UV 254 that is approximately equivalent to the loss of virus infectivity (5,18,27), implying a minimal contribution of protein damage to overall virus inactivation. While this is ideal for studies wishing to use qPCR tools as a rapid alternative to cell culture for estimating loss of infectivity, from a mechanistic standpoint these data diminish the importance of potential protein damage, which, based on the present study, may play a larger role than previously concluded.…”
Section: Discussionmentioning
confidence: 85%
“…RT-qPCR verification was performed with a previously established qPCR primer set (19) consisting of forward primer 3F (5=-ACT TTGGGTGTCCGTGTTTC-3) and reverse primer 4R (5=-TACTCAGGCCATCGACCATAC-3=). RT-qPCR was performed on an MIC qPCR machine (BioMolecular Systems) utilizing a One-Step TB Green PrimeScript RT-PCR kit (Perfect Real Time) (TaKaRa, Clontech) according to previously established cycling conditions (5). The infection by E11 was considered successful if the E11 genome copy number in a well was greater than the originally transfected E11 RNA concentration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, from a regulatory point of view, a significant barrier exists, as there is no one disinfectant method which is effective against all viruses and can be utilised or applied to all water quality conditions. [51], [116]. An in-depth understanding of the mechanisms which are involved in virus inactivation is still needed if the scientific community wants to be able to predict the susceptibility of nonculturable virus strains to different disinfectants.…”
Section: Virusmentioning
confidence: 99%